Pengaruh Akun Instagram @temandisabilitas_Id dalam Meningkatkan Kesadaran Followers Terhadap Difabel - Angelita Kania Ramdan; Fuad Rizki Rismawan; Nadiah Wiharnis; Dini Safitri (Inter Komunika, 2019)
The Instagram account @temandisabilitas_id uses Instagram as a media to provide information about people with disabilities, to provide knowledge to followers of the account about people with disabilities. This account presents attractive content with a variety of visual and audiovisual content. The purpose of this study was to determine the effect of this Instagram account on increasing knowledge of @temandisability_id account followers. This study uses the influence variable Instagram social media, which has two dimensions, namely content and increased knowledge. This research uses a quantitative approach, with a descriptive type of research. The population is 192 with a sample of 59. The results of this study indicate that the information provided by the account has an influence on increasing the knowledge of Instagram account followers @ dependability. Because the content is short and clear and interesting.